Augustus Earle in New Zealand: An Early Colonial Artistic Perspective - Moon, Paul (Te Kaharoa, 2015)
This article surveys the events and individuals encountered by the English artist Augustus Earle (1793 -1838) during his visit to New Zealand in 1827-8. Through his paintings, Earle offers one of the first comprehensive European artistic impressions of parts of New Zealand and its inhabitants prior to the onset of large-scale British colonisation. Many of his conclusions and perspectives were unavoidably subjective, but they at least offer a glimpse into one person’s impression of the country at this time.